Back to Where It All Began: Revisiting Algonquin Resource Use and Territoriality - Inksetter, Leila (Anthropologica, 2018)
This article examines resource use among the Algonquin and its change over time. Archaeological and historical data show that the current importance of the moose for both food and clothing among Algonquin people is a relatively recent phenomenon: in pre-contact times up until the nineteenth century, small mammals such as beaver and hare were the most important animals used. The dichotomy between access rights to moose and fur-bearing animals also seems to be a recent phenomenon. As this dichotomy has been used as a major element in theoretical reconstructions of past territoriality and governance, this re-evaluation thus offers a renewed perspective on the history of family hunting territories among Algonquian peoples.